Paracrine WNT5A Signaling in Healthy and Neoplastic Mammary Tissue. (2nd January 2016) - Kusner, David; Borcherding, Nicholas; Zhang, Weizhou
ABSTRACT: Paracrine signaling between mammary epithelial cells has long been appreciated. Recently, we found that Wnt5a, a novel noncanonical Wnt ligand of luminal origin, counteracts canonical Wnt signaling in basal mammary epithelial cells through a paracrine pathway, inhibits the expansion of Erbb2-induced tumor-initiating cells, and suppresses tumor incidence and metastasis.